THE PROBLEM OF MODELING THE DISPERSION OF THE HEAVY HYDROCARBONS VAPOUR'S OF EMISSIONS AND SIZE'S JUSTIFICATION OF THE SANITARY PROTECTION ZONE FOR GAS FILLING STATIONS - Sergey A. Koshkarev; Ekaterina V. Sokolova; Pavel A. Sidyakin (Современная наука и инновации)
This article describes an approach to improve modeling the dispersion of heavy hydrocarbon va-por emissions of gas filling stations in the atmosphere. It was considered the problem of the size’s justi-fication of the of the sanitary protection zone of gas filling stations. The article presents the results of field measurements and calculations of emissions of air pollutants from the gas station within the ur-banized areas of Russian cities. There is comparison the results of concentration’s measurements of dangerous substances at the gas-supplying complexes’ territories and the board human habitants and modeling results stratifications emissions’ pollutions in the atmosphere in this article. It was made the conclusion about the feasibility of accounting for regulations of size of the sanitary protection zone gas filling station technology including fuel- injection -gas filling process in tanks. Based on the analysis of the concentration derived from the results of field measurements and calculations of emissions, con-cluded that the need for dispersion calculations of heavy hydrocarbon vapor in the atmosphere for var-ious physical parameters of the source of emissions - gas filling station. There was made conclusion about perspective ways of reduction emissions of dangerous pollutions on these gas-supplying com-plexes’